Virtual Exhibition of PGMI IAIN Ambon Students Through Technical Assistance and Procedures for Exhibiting Fine Artwork During the Covid-19 Pandemic - Iga Ayu Intan Candra (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Abstract: The Covid-19 pandemic has interrupted the artistic process that occurs in society. Making people forced to use digital platforms in the process of expression and appreciation of art. During the Covid-19 pandemic, fine arts chose digital media as a way out for the exhibition. This community service is one solution to increase the expression and appreciation of PGMI IAIN Ambon students who will later teach art as classroom teachers. The service activity with the title "Virtual Exhibition of PGMI IAIN Ambon Students Through Technical Assistance in Crafting and Procedures for Exhibiting Fine Artwork During the Covid-19 Pandemic" seeks to create students who are aware of the values of artistic and are able to create works of art. Activities are carried out through a process of assisting work and assisting the process of implementing virtual exhibitions.Keywords: fine art, exhibition, virtual, covid-19Abstrak: Pandemi Covid -19 telah memutus proses kesenian yang terjadi di masyarakat. Membuat masyarakat terpaksa menggunakan platform digital dalam proses ekspresi dan apresiasi seni. Seni rupa pada masa pandemi Covid-19 memilih media digital sebagai jalan keluar pelaksanaan pameran. Pengabdian masyarakat ini merupakan salah satu solusi untuk meningkatkan ekspresi dan apresiasi mahasiswa PGMI IAIN Ambon yang nantinya akan mengajar seni sebagai guru kelas. Kegiatan pengabdian dengan judul kegiatan “ Pameran  Virtual Mahasiswa PGMI IAIN Ambon Melalui Pendampingan Teknik Berkarya dan Prosedur Memamerkan Hasil Karya Seni Rupa Selama Pandemi Covid-19” berupaya mewujudkan mahasiswa yang sadar akan nilai-nilai keindahan dan mampu menciptakan karya seni rupa. Kegiatan dilaksanakan melalui proses pendampingan berkarya dan pendampingan proses pelaksanaan pameran secara virtual.Kata kunci: seni rupa, pameran, virtual, covid-19